Control of invasive rats on islands and priorities for future action. Issue 4 (18th April 2017) - Duron, Quiterie; Shiels, Aaron B.; Vidal, Eric
Abstract: Invasive rats are one of the world's most successful animal groups that cause native species extinctions and ecosystem change, particularly on islands. On large islands, rat eradication is often impossible and population control, defined as the local limitation of rat abundance, is now routinely performed on many of the world's islands as an alternative management tool. However, a synthesis of the motivations, techniques, costs, and outcomes of such rat‐control projects is lacking. We reviewed the literature, searched relevant websites, and conducted a survey via a questionnaire to synthesize the available information on rat‐control projects in island natural areas worldwide to improve rat management and native species conservation. Data were collected from 136 projects conducted over the last 40 years; most were located in Australasia (46%) and the tropical Pacific (25%) in forest ecosystems (65%) and coastal strands (22%). Most of the projects targeted Rattus rattus and most (82%) were aimed at protecting birds and endangered ecosystems. Poisoning (35%) and a combination of trapping and poisoning (42%) were the most common methods. Poisoning allows for treatment of larger areas, and poison projects generally last longer than trapping projects. Second‐generation anticoagulants (mainly brodifacoum and bromadiolone) were used most often. The median annual cost for rat‐control projects was US17, 262 or US227/ha. Median project duration was 4 years. For 58% of the projects, rat population reduction was reported, and 51% of projects showed evidence of positive effects on biodiversity. Our data were from few countries, revealing the need to expand rat‐control distribution especially in some biodiversity hotspots. Improvement in control methods is needed as is regular monitoring to assess short‐ and long‐term effectiveness of rat‐control.